TEKNIK PENGEMBANGAN BARIER EKOLOGI UNTUK MENEKAN LAJU PERAMBAHAN HUTAN PENDIDIKAN STIK DI JANTHO - Ruskhanidar; Rosmalia; Cut Nelly (Lembaga Riset dan Inovasi Kreyat Center, 2025)
The Jantho STIK educational forest is an important habitat for the kedih primate species (Presbytis thomasi), the gray langur (Christatus auratus), and the long-tailed macaque (Macaca fascicularis). The destruction of these primate habitats through forest encroachment is also carried out by the community around the educational forest. The conservation status for these three species is listed as vulnerable in the IUCN and Appendix II in CITES. They are protected animals. Habitat disturbance in the form of forest encroachment is often carried out by the community. This encroachment results in a decline in the quality of primate habitats, due to the loss of food sources and the loss of sleeping trees. In order for the protection of primate species and habitats to take place properly, and the economic value of the community can increase with the presence of primates, as well as to suppress the rate of forest encroachment, it can be done by building ecological barriers in the primate habitat. This ecological barrier is basically made to improve the habitat of wildlife that is experiencing fragmentation. In addition, it is to keep wildlife in their home range, and not to leave their habitat into community agricultural areas. The community service was conducted on August 22-24, 2025, at the STIK education forest in Boeng Jantho village. Community service included socialization of ecological barriers, planting vegetation on ecological barriers, mentoring, evaluation and monitoring. The ecological barrier was made in an area of ​​one hectare and planted with types of vegetation that are not favored by primates (pine, sugar palm and candlenut). The community's enthusiasm was quite high to participate in the socialization and planting. The vegetation developed on ecological barriers can control animals from leaving their natural habitat, so that hunting can be suppressed and forest encroachment can decrease.